PENGARUH KEPUASAN KERJA, FASILITAS KERJA DAN STRES KERJA TERHADAP KINERJA PERSONIL PLETON I YONKAV 6/NK KODAM I BUKIT BARISAN - Yudi Prasetio (Manajemen dan Bisnis, 2020)
The term of this study is: Does the job satisfaction, work facility and work stress affect on employee performance  at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN. The aim of the study is to determine the effect of job satisfaction, work facility and work stress of employees performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN.The sample of this study were 50 employees at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN. The technique of the data analysis in this research is Multiple Linier Regression Analysis. The results of this study show that job satisfaction  has a positive and significant influence on Employee Performance; Work Facility has a positive and significant influence on Employee Performance; Work stress  has a negative and significant influence on Employee Performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN, finally job satisfaction, work facility and work stress simultaneously have a significant effect on Employee Performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN.